2012
DOI: 10.1063/1.3675970
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon-enhanced electroluminescence in organic light-emitting diodes incorporating Au nanoparticles

Abstract: Surface plasmon-enhanced electroluminescence (EL) in an organic light-emitting diode is demonstrated by incorporating the synthesized Au nanoparticles (NPs) in the hole injection layer of poly(3,4-ethylene dioxythiophene):polystyrene sulfonic acid. An increase of ∼25% in the EL intensity and efficiency are achieved for devices with Au NPs, whereas the spectral and electrical properties remain almost identical to the control device. Time-resolved photoluminescence spectroscopy reveals that the EL enhancement is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
123
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 31 publications
2
123
0
Order By: Relevance
“…Similar EL enhancements have been observed by others when thermally evaporating metal ultrathin film or nanoclusters onto ETL or HBL. [18][19][20] Xiao et al 21 have also found a similar increase in the EL intensity and efficiency when incorporating as-synthesized spherical Au nanoparticles (NPs) into the hole injection layer of poly (3,4-ethylenedioxythiophene) with poly(4-styrenesulfonate) (PEDOT:PSS). However, Liu et al 22 found no performance improvement on the luminescence efficiency when burying 2 nm thermally evaporated gold NPs into HTL 4,4 ′ -bis[N-(1-naphthyl-1-)-N-phenyl-amino]-biphenyl, although they carefully adjusted the distance between the NPs and the EML.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar EL enhancements have been observed by others when thermally evaporating metal ultrathin film or nanoclusters onto ETL or HBL. [18][19][20] Xiao et al 21 have also found a similar increase in the EL intensity and efficiency when incorporating as-synthesized spherical Au nanoparticles (NPs) into the hole injection layer of poly (3,4-ethylenedioxythiophene) with poly(4-styrenesulfonate) (PEDOT:PSS). However, Liu et al 22 found no performance improvement on the luminescence efficiency when burying 2 nm thermally evaporated gold NPs into HTL 4,4 ′ -bis[N-(1-naphthyl-1-)-N-phenyl-amino]-biphenyl, although they carefully adjusted the distance between the NPs and the EML.…”
Section: Introductionmentioning
confidence: 94%
“…[7][8][9][10][11][12] According to Purcell effect, effective dipole-surface energy transfer takes place between excitons and SPs, thus creating a new channel for emission and resulting in increase in spontaneous emission rate and emission intensity. [13][14][15] To date various methods including surface plasmon polaritons (SPPs) and localized surface plasmons (LSPs) have been developed to induce SPs in order to enhance EL intensity in OLEDs. Here, SPPs and LSPs are respectively induced by periodic metal nanostructures with continuous surfaces and discrete metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…3a, indicate that the exciton lifetime of nanocomposite (10.692 ns) is shorter than that of the PEHF layer (11.651 ns). Xiao et al [14] has explained that the coupling process between the surface plasmons and the emitted light occurs when the exciton lifetime is shorter, compared with that of the the emitted light of the polymer. Further criterium of coupling between the surface plasmons and the emitted light is that the absorption peak of metal nanoparticles and the photoluminescence peak of the emitting layer must nearly overlap [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…The SPRE of metal nanoparticles or nanoclusters can reduce the excitons lifetime of the device, resulting that the spontaneous emission rate of the device is increased [10]. Besides, the gold nanoparticles (GNPs) are doped into hole-transport layer (HTL), resulting in increasing in the efficiency of the device, but it only adopts unitary size for GNPs [11]. Nevertheless, the different varieties, sizes, and shapes for nanoparticles will generate different surface plasmon resonance effects in the devices.…”
Section: Introductionmentioning
confidence: 99%